THE СONCEPTUAL FRAMEWORK OF PUBLIC-PRIVATE PARTNERSHIP IN UZBEKISTAN - Akbarov , Gayratjon Nemadjonovich (Educational Research in Universal Sciences, 2024)
This article describes the forms of public-private partnership, the main directions of economic and social cooperation between the state and business entities, the term "public-private partnership" and its economic essence, the advantages of implementing public-private partnership projects done.